Rural schools in Peru: factors that accentuate the digital gaps in times of pandemic (COVID-19) and recommendations to reduce them - Anaya Figueroa, Tania (2021)
This study points out factors that deepen the digital gaps in rural schools in Peru in the context of the COVID-19 pandemic. Thus, basic rural education is addressed before and during the pandemic a few factors that intensify the digital gaps, existing inclusion policies and several recommendations to reduce them. It is a qualitative, analytical-descriptive study, with comparative elements between urban and rural, specifically in the Andean region of Peru. Some factors accentuate the digital gaps, such as connectivity, devices, appropriation of technology, and inadequate teacher training, among others. The study highlights the need to enhance the binomial connectivity and teacher training for the use of communication and information technologies and for intercultural dialogue in the learning processes.